O Voleibol nas aulas de Educação Física no Ensino Médio Integrado: uma possibilidade pedagógica a partir da abordagem crítico-emancipatória - Araújo, João Maria Dias e Silva (2024)
Considering the diversity of cultural manifestations that can be thematized, sport continues to be prominently featured, being a content that provides a range of movements to be explored and experienced in High School Physical Education classes. In this scenario, volleyball is a traditional and popular sports discipline among young people that can be themed in different ways, using other scenarios and contexts, bringing new learning possibilities, mainly when worked in a critical approach to Physical Education, as the critical-emancipatory approach, which seeks to put students at the center of the teaching-learning process and stimulates them in the development of autonomy, protagonism, creativity, and critical thinking. In this context, the present research aims to analyze a pedagogical intervention materialized in the classes of Integrated High School Physical Education with the volleyball content from the criticalemancipatory approach. The specific objectives are to develop a didactic unit on volleyball through the critical-emancipatory approach, to evaluate the teachinglearning process of the applied proposal, and to elaborate a teaching notebook with the volleyball content, through the critical-emancipatory approach, as an educational product. For this purpose, a descriptive, qualitative, and intervention type of research was carried out, targeting 26 students from the 2nd year of the Integrated Technical High School from the Morning Environmental Control Course at the Federal Institute of Education, Science, and Technology of Rio Grande do Norte – Natal Central Campus (Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte – Campus Natal Central), in the city of Natal/RN. The didactic unit was composed of ten meetings. For data collection, the researcher’s field diary, participant observation, and portfolio were used as instruments. Data analysis was divided into three main topics: (1) Known Volleyball: aimed to describe the first meeting of the didactic unit and to identify students’ prior knowledge about volleyball; (2) Experienced Volleyball: aimed to describe the other nine meetings; and (3) Perceived Volleyball: related to the evaluation of the teaching-learning process. As results, regarding the volleyball known by the students, it was identified that the main aspects related to the discipline were about rules, fundamentals, game situations, and curiosities. Regarding the volleyball experienced by the students, it is noticeable that the experiences generated opportunities to experiment, learn, and create/invent many possibilities about volleyball. In the perceived volleyball, students pointed out that the volleyball theming was diverse, new, positive, and inclusive; that students’ participation throughout the meetings was considered very expressive; and that the pedagogical intervention was important for their integral formation through reflection, satisfaction, and growth. Therefore, it is considered that the proposed pedagogical intervention was quite successful, and the critical-emancipatory approach proves to be a potent and fruitful possibility for developing any content of Physical Education in the Integrated High School Physical Education. Thus, it is believed that the results presented in this dissertation and the product generated can be reflected, replicated, and reconstructed by other researchers in new contexts and with different audiences.